The tailypo : a ghost story - Galdone, Joanna; Galdone, Paul. (New York : Seabury Press, 1977)
A strange varmint haunts the woodsman who lopped off its tail.
"A Clarion book."
School Library Journal
School Library Media Quarterly (A.A.A.L.)
Library Journal
3.6
K-3
Keywords: Folklore -- United States; Folklore -- United States